Short distance analysis of the 400-meter walk test of mobility in community-dwelling older adults - Krumpoch, Sebastian; Lindemann, Ulrich; Becker, Clemens; Sieber, Cornel; Freiberger, Ellen (Gait & Posture, 2021)
Background: The 400-meter walk test (400MWT) is used to assess cardiovascular and pulmonary fitness or to predict adverse outcomes such as mobility disability. Additionally, short tests of walking such as the 4- or 8-meter walk test are administered to predict mortality, falls and other events. It remains uncertain if and how an integrated measurement of a short distance during 400MWT can replace an additional short distance measurement which would be clinically useful. Research question: How do short distance (i.e. segment) measurements of gait speed and walk ratio during a 400MWT of mobility compare to those from an additional 8-meter walk test? Methods: A 400MWT and a separate 8-meter walk test were performed by 148 community-dwelling older adults (mean age 80.4 ± 4.4 years) using an instrumented walkway. Results: Gait speed and walk ratio (i.e. step length divided by step frequency) of single segments of the 400MWT were strongly associated with gait speed (r ≥ 0.91) and walk ratio (r ≥ 0.93) of an 8-meter walk test with best agreement in the middle part 20-meter walk during the 400MWT. Mean gait speed of all single walks on the instrumented walkway during the 400MWT was faster than the mean gait speed of the total 400MWT. Significance: A single walk of the 6th to 10th 20-meter walk during the 400MWT can be used as a substitute to an additional short distance trial. Furthermore, the awareness of being measured is higher on an instrumented walkway and possibly increases the motivation to overperform.
CRIS-Team Scopus Importer:2021-05-21
Keywords: 400-meter walk test; Awareness; Gait speed; Older adults; Walk ratio